2004
DOI: 10.1614/p2002-053
|View full text |Cite
|
Sign up to set email alerts
|

Seed germinability and its seasonal onset of Japanese knotweed (Polygonum cuspidatum)

Abstract: Sexual reproduction is known to be an important means of propagation for native Japanese knotweed populations in Asia. For naturalized populations in the United States, however, its relative importance compared with propagation by rhizome and stem fragments has not been established. This article presents two related studies that address two basic questions regarding the potential for propagation by seed: (1) are seeds that are produced by Japanese knotweed in areas of Philadelphia, PA, capable of germinating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…and also created some most unexpected hybrids between highly divergent parents. In terms of threats posed, F. x bohemica and its backcrosses are of major importance, particularly in North America (Bram and McNair, 2004), where recruitment from seed is much more common than in Europe. F. x conollyana, inspite of its frequent production as seed, rarely germinates in the wild and even when it does, is not a very strong competitor.…”
Section: Discussionmentioning
confidence: 99%
“…and also created some most unexpected hybrids between highly divergent parents. In terms of threats posed, F. x bohemica and its backcrosses are of major importance, particularly in North America (Bram and McNair, 2004), where recruitment from seed is much more common than in Europe. F. x conollyana, inspite of its frequent production as seed, rarely germinates in the wild and even when it does, is not a very strong competitor.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum germination was generally achieved after lateSeptember, with seeds from some sites reaching maximal germination in late October (Bram and McNair 2004). However, maximum percentage germination varied drastically (40->90%), which may be due to either intraspecific variation in seed germinability or sites containing different Polygonum species, since identification to species was not confirmed.…”
Section: Reproductionmentioning
confidence: 97%
“…(c) Seed Banks, seed Viability and Germination - Bram and McNair (2004) showed that a moist chilling (4°C) of 30 d immediately after mid-September through mid-October seed collection generally increased maximum percent germination compared with the same stratification treatment given the following year in Philadelphia, PA populations. Maximum germination was generally achieved after lateSeptember, with seeds from some sites reaching maximal germination in late October (Bram and McNair 2004).…”
Section: Reproductionmentioning
confidence: 99%
See 2 more Smart Citations